Cyberbullying victimization prevalence and associations with internalizing and externalizing problems among adolescents in six European countries - Tsitsika, A.; Janikian, M.; Wójcik, S.; Makaruk, K.; Tzavela, E.; Tzavara, C.; Greydanus, D.; Merrick, J.; Richardson, C. (2015)
Cyberbullying victimization is an important adolescent health issue. The cross-national study aimed to investigate the prevalence of cyber victimization and associated internalizing, externalizing and academic problems among adolescents in six European countries. A cross-sectional school-based study of 14-17 year-old adolescents (N = 10,930; F/M: 5719/5211; mean age 15.8 ± 0.7 years) was conducted in Spain, Poland, the Netherlands, Romania, Iceland and Greece. In total, 21.4% of adolescents reported cyber victimization in the past 12 months. Reports were more frequent among girls than boys (23.9% vs. 18.5%), and among the older adolescents compared to the younger ones (24.2% vs. 19.7%). The prevalence was highest in Romania and Greece (37.3% and 26.8%) and lowest in Spain and Iceland (13.3% and 13.5%). Multiple logistic regression analysis indicated that cyber victimization was more frequent among adolescents using the internet and social networking sites for two or more hours daily. Multiple linear regression analysis showed that externalizing, internalizing and academic problems were associated with cyber victimization. Overall, cyber victimization was found to be a problem of substantial extent, concerning more than one in five of the studied European adolescents. Action against cyber victimization is crucial while policy planning should be aimed at the prevention of the phenomenon. © 2015 Elsevier Ltd.